High-speed non unit transmission line protection using single-phase measurement and an adaptive wavelet: Zone detection and fault classification - Pérez, Fabián; Aguilar, Rommel; Orduña, Eduardo; Jäger, Johann; Guidi-Venerdini, Guillermo (IET Generation Transmission & Distribution, 2012)
This work describes a transmission line protection scheme with two protection functions: directional zone and fault classification. The proposed scheme requires no information from remote ends and uses current measurements of only one phase of the three-phase systems for determining the fault direction, the faulted line and the fault type. Information concerning the high-frequency components of transient current signals is extracted with discrete wavelet transform (DWT) by using an adaptive wavelet, which has been specifically designed for relaying purposes, as analysis filter. After that, Bayesian linear discriminant analysis is employed for data classification. The present work highlights that the adaptive wavelet used here presents advantages for transmission line protection rather than predefined mother wavelets. Results demonstrate that the proposed scheme effectively distinguishes the faulted zone, the fault direction and the fault type. Therefore it offers primary protection to total line length, remote backup protection for the next transmission line and also the possibility to implement single-pole tripping. Current signals of roughly 2 ms are analysed then the proposed methodology can be implemented in high-speed protection schemes for extra- and ultra-high voltage (EHV/UHV) networks.<br
Keywords: discrete wavelet transforms; power transmission faults; power system measurement; fault diagnosis; Bayes methods; power transmission lines; adaptive filters; power filters; power transmission protection